Quality of Maternal Parenting of 9-Month-Old Infants Predicts Executive Function Performance at 2 and 3 Years of Age - Cheng, Nanhua; Lu, Shan; Archer, Marc; Wang, Zhengyan (Frontiers in Psychology, 2018)
Whereas the effects of maternal parenting quality during infants’ 2nd year on later executive function (EF) have been studied extensively, less is known about the impact of maternal parenting quality during the 1st year. The aim of this study was to examine whether maternal parenting during infants’ 1st year predicted EF performance at 2 and 3 years of age in a Chinese sample. Data were collected from 96 mother-infant dyads (42 males) when the infants were 6, 9, 25, and 38 months old. Cognitive development as a control variable was measured with the Bayley Scales of Infant Development II at 6 months. At 9 months, three aspects of maternal parenting quality (sensitivity, mind-mindedness, and encouragement of autonomy) were assessed with MBQS, mind-mindedness coding system, and encouragement of autonomy coding schema within a 15-min mother–infant interaction. Three aspects of EF (working memory, inhibitory control, and delay EF) were measured at 25 and 38 months with age-appropriate tasks. Hierarchical regression analysis showed that maternal mind-mindedness had a more important effect than did the encouragement of autonomy and maternal sensitivity during infants’ preverbal period. More precisely, maternal mind-mindedness at 9 months predicted inhibitory control at 2 and 3 years, and maternal encouragement of autonomy predicted performance on delay EF tasks at 3 years, maternal sensitivity had no observed effect on children’s EF. This study suggests that maternal parenting quality during the 1st year (maternal mind-mindedness and encouragement of autonomy, but not maternal sensitivity) impacts later EF development.